Novel entropy–stabilized ultra high temperature ceramics thin films prepared by magnetron sputtering; 6th International Congress on Energy Fluxes and Radiation Effects; 3rd International Conference on New Materials and High Technologies (3rd NMHT), November 2018 - Demchenko S. G. Stanislav Gennadjevich; Zelentsov D. Yu. Denis Yurjevich; Linnik S. A. Stepan Andreevich; Gaydaychuk A. V. Alexander Valerievich; Zenkin S. P. Sergey Petrovich (2018, 2018)
Title screen